Deissi. Un possibile nesso linguistica-estetica-ontologia - Roberto Diodato (Aisthesis, 2012)
The essay  concerns the relationship between aesthetics and onthology. It starts from the analysis of a particularity of the ordinary speech: the deixis. Shifters or indicators are personal and dimostrative pronouns  that means an entity presence in its quality of actus essendi. According to Roberto Diodato the strength of the deixis is particulary vivid in  the aesthetics experience. The author reaches this conclusion through the discussion with the most important philosophers who studied this subject.